Prisons, mental health and mindfulness : which therapies have been working internationally and how could they be used in Icelandic prisons? - Anton Björn Christensen 1989- (2021)
Verkefnið er lokað til 30.05.2025. Prisoners generally tend to have a higher rate of depression, self-reported life dissatisfaction and attempted suicide compared to the general population. In recent years, the spotlight has been aimed more often towards the mental health of prisoners of the world, but not much documented research on mental health of prisoners in Iceland exists. In 2019 a task force was formed, with the aim and focus being on increasing psychiatric service provided to prisoners in Iceland, and giving them more assistance, support, and follow-up once they finish their sentence. The literature that existed on this topic before the task force was formed is lacking in variety, with majority of it focusing on ADHD and not much on other mental disorders. At least 83% of Icelandic prisoners have experienced at least one type of maltreatment while growing up, with 47,9% experiencing sexual abuse. There is great need for further research in the prisons in Iceland so a comparison can be made with prisons internationally, implement clinical instructions and integrate with other parts of health care that is available in prisons. Therapies that have shown to have a positive effect in prisons include art therapy, meditation, cognitive behaviour therapy (CBT), Dialectical Behaviour Therapy (DBT), and mindfulness. Many different types and definitions of mindfulness exist, but most describe mindfulness as the ability to combine breathing and meditation techniques with CBT. Training in mindfulness has shown to have an especially positive effect in a minimum-security prison. Those include reduced recidivism rates, higher self-esteem, fewer cases of violence, less depression and anxiety compared to groups with no training, but the therapy of choice must be made after careful consideration of the type of inmates in question and type of correctional facility. Keywords: Prisoners, mental health, mindfulness, therapy, recidivism, psychiatric service. Fangar sýna almennt hærri tíðni af þunglyndi, óánægju með líf ...